Minocycline mitigates Aβ and TAU pathology, neuronal dysfunction, and death in the PSEN1 E280A cholinergic-like neurons model of familial Alzheimer’s disease (2024)
ABSTRACT: Familial Alzheimer's disease (FAD) presenilin 1 E280A (PSEN1 E280A) is a severe neurological condition due to the loss of cholinergic neurons (ChNs), accumulation of amyloid beta (Aβ), and abnormal phosphorylation of the TAU protein. Up to date, there are no effective therapies available. The need for innovative treatments for this illness is critical. We found that minocycline (MC, 5 μM) was innocuous toward wild-type (WT) PSEN1 ChLNs but significantly (i) reduces the accumulation of intracellular Aβ by -69%, (ii) blocks both abnormal phosphorylation of the protein TAU at residue Ser202/Thr205 by -33% and (iii) phosphorylation of the proapoptotic transcription factor c-JUN at residue Ser63/Ser73 by -25%, (iv) diminishes oxidized DJ-1 at Cys106-SO3 by -29%, (v) downregulates the expression of transcription factor TP53, (vi) BH-3-only protein PUMA, and (vii) cleaved caspase 3 (CC3) by -33, -86, and -78%, respectively, compared with untreated PSEN1 E280A ChLNs. Additionally, MC increases the response to ACh-induced Ca2+ influx by +92% in mutant ChLNs. Oxygen radical absorbance capacity (ORAC) and ferric ion-reducing antioxidant power (FRAP) analysis showed that MC might operate more efficiently as a hydrogen atom transfer agent than a single electron transfer agent. In silico molecular docking analysis predicts that MC binds with high affinity to Aβ (Vina Score -6.6 kcal/mol), TAU (VS -6.5 kcal/mol), and caspase 3 (VS -7.1 kcal/mol). Taken together, our findings suggest that MC demonstrates antioxidant, anti-amyloid, and anti-apoptosis activity and promotes physiological ACh-induced Ca2+ influx in PSEN1 E280A ChLNs. The MC has therapeutic potential for treating early-onset FAD.